SISTEM INFORMASI PARIWISATA KABUPATEN MAGELANG BERBASIS WEB - Handayani Handayani; Wasino Wasino; Desi Arisandi (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Magelang is the Regency of Central Java Province. As a tourist destinations, Magelang has a lot of natural resources, culture, and exciting attractions. Tourism sector is one of aspect that can increase local revenue. Currently, the potential development of the tourist area in Magelang is still not widely known by the public, both inside and outside of the country. The tourists will have difficulty in determining travel planning because the information provided is not complete. Travelers need information systems that is more rapid, precise, and complete so that travelers know the description of tourist areas to be visited. The data is being collected by using purposive sampling method. Testing the credibility of the data with source triangulation techniques. The programming language used HTML, PHP, and CSS. Database used MySQL and the XAMPP Control Panel as a server at localhost. The data collected through interviews and observation in Magelang Regency.Tourism Information System Magelang Regency Based Web has been implemented so that visitors can find out information location on tourist attraction, tourist services (hotel, gas station, and restaurant), and directions road using Google Maps. This system also can be used as a means of travel guides for tourist who visit and can help in publicizing tourism potential in the Regency of Magelang